Soil organic carbon stock of major agricultural land use types in Bukidnon, Philippines - Patricio, Jose Hermis P. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2014)
This study determined the soil carbon sequestration potential of major agricultural land use types in Bukidnon, Philippines which included plantation of corn, rice, sugarcane, pineapple, banana, rubber, cassava, coconut, coffee, and mango. Field measurement of soil organic carbon (SOC) stock was adopted with modification using the sampling protocol described by Hairiah, Sitompul, Van Noordwijk, and Palm (2001). Among the ten land use types examined, rubber and coconut plantations showed significantly the highest soil organic carbon sequestered amounting to 37.1 MgC ha-1 and 30.3 MGC ha-1, respectively while pineapple plantation had the least at 14.7 MgC ha-1. Although theoretically SOC decreases with soil depth, there is no significant variation among soil depths at 10 cm, 20 cm, and 30 cm in terms of their ability to store organic carbon in this study. These findings need to be communicated to policymakers to institutionalize interventions that are necessary to keep or increase further the existing carbon stocks in these agricultural land areas.